Protestant Millennialism, Evangelicalism and Irish Society, 1790-2005
XII, 244 p.
Keywords: This volume documents the evolution and impact of one of the most enduring sources and symbols of sectarian conflict in Ireland - Protestant millennialism. The volume explores new sources and offers new conclusions, setting a new research agenda and emphasizing the vitality of religious discourse in Irish studies.